Penilaian program Ijazah Sarjana Muda Perguruan (PISMP) Matematik di Institut Pendidikan Guru Malaysia zon utara - Syed Khalid, Syed Idrus @ Sd Iskandar (2018)
Bachelor of Teaching Mathematics (PISMP) is one of the programmes offered at Teachers Trainee Institute. Previous studies have shown there are Mathematics teachers who encounter problems with the content knowledge and Mathematical pedagogical knowledge in teaching and learning sessions. The reevaluation of teacher training programmes needs to be conducted in order to prepare data to add value to the programmes and to improve the quality of teacher trainings. The objective of this study is to evaluate the implementation of PISMP programmes using CIPP Model by focusing on the suitability of the curriculum, basic learning facilities, learning support, educational resources, teaching quality, assessment, skills, knowledge and satisfaction of trainee teachers towards the programmes. The research method used is a mix method (MMR) which is quantitative and qualitative method. Survey and interviews were used to obtain data from five IPG in Northern Region on the perception of trainee teachers on the PISMP programmes. Whole population of Northern Region PISMP Mathematics which is 187 trainee teachers were involved in answering questionnaires while five were involved in semistructured interviews. The findings show that the respondents’ assessment of the suitability of the curriculum is high. The quality of teaching, assessment, knowledge, skills and satisfaction of trainee teachers are also high. Assessment of basic facilitation aspects, learning support and the educational resources provided by IPGM is moderate. Multiple Regression testing indicate the influence of teaching quality and assessment on skills (36.0%), on knowledge (33.2%) and on satisfaction (29.0%). Similarly, the influence of basic facilities, learning support, and educational resources on satisfaction (32.1%), on knowledge (14.4%), and on skills (11.7%). The study indicates the importance of curriculum, basic facilities, learning support, educational resources, teaching quality and assessment towards knowledge, skills and satisfaction of trainee teachers which studied PISMP Mathematics programmes in teacher training institutes. This study also provides data on the implementation of the PISMP Mathematics programmes at IPG. Research data can be used in teacher training programmes since well conducted teacher trainings will produce great teachers.